The Effect Of Government Policy And Environmental Sustainability On The Performance Of Tourism Business Competitiveness: Empirical Assessment On The Reports Of International Tourism Agencies - Susanto, Alfonsus Budi (International Journal of Energy Economics and Policy, 2019)
There is a very close relationship between tourism growth, government policy support, and environmental preservation obligations. In the context of strategic management, this research focuses on government policy, and tourism resource such as environmental, socioeconomic and cultural factors for increasing tourism business competitiveness and its implication on the performance of tourism business using explanatory survey with unit analysis countries listed in both Travel and Tourism Competitiveness Report (TTCR, 2011) of World Economic Forum and World Travel and Tourism Council (WTTC, 2011). This study used Partial Least Square (PLS) for statistical analysis. Data collections are conducted through latest secondary data from TTCR and WTTC, which include data and findings regarding government policy, tourism resource, tourism business competitiveness, and the performance of tourism business players. The research findings show that government policy has correlation with tourism resource and government policy and tourism resource simultaneously influence tourism business competitiveness. Partially, tourism resource dominantly influences business competitiveness if compared to government policy, tourism business competitiveness influences the performance of tourism businesses, and government policy and tourism resource directly influence the performance of tourism business. Partially, government policy dominantly influences the performance of tourism business if compared to tourism resource. Government policy and tourism resource influence the performance of tourism business through business competitiveness. Keywords: government policy, environmental factors, tourism research, tourism business competitiveness, business performance. JEL Classifications: Z31, Z32 DOI: https://doi.org/10.32479/ijeep.8297